Safeguarding Consumers through Minimum Quality Standards: Milk Inspections and Urban Mortality, 1880-1910 - D. Mark Anderson; Kerwin Kofi Charles; Michael McKelligott; Daniel I. Rees (Institute of Labor Economics (IZA), 2022)
We examine the effect of enforcing minimum quality standards (MQSs) on consumer health. In the late 1800s, the urban milk supply was regularly skimmed and diluted with water, but consumers could not easily determine its quality because dyes, caramel, and salt were added. To protect consumers, milk inspectors were tasked with enforcing a well-defined MQS. Using city-level data for the period 1880-1910, we find that milk inspections reduced mortality from waterborne and foodborne diseases by 8-19 percent. Ours is the first study to provide evidence that MQSs can improve consumer health when directly applied to an experience or credence good.
Keywords: H75; I18; J18; L51; N31; 330; milk inspections; infant mortality; waterborne mortality; urban mortality